Variations in the union of the ductus cysticus with the ductus hepaticus communis - Figen GÖVSA; Z. Aslı AKTAN; Tuncay VAROL; Hasan UÇKAN; Yücel ARISOY; Yılmaz ŞENYILMAZ (Turkish Journal of Gastroenterology, 2019)
-